Studies on the Pathogenesis of the Generalized Shwartzman Reaction - Rodríguez-Erdmann, F (Thrombosis and Haemostasis, 1964)
The generalized Shwartzman reaction (gSr) was produced in pregnant rabbits by means of a single intravenous injection of E.-coli endotoxin. The animals developed a profound and a haemorrhagic diathesis. The haemorrhagic condition is thought to be the result of an acute consumption of the plasma-factors of the coagulation system. The pathogenesis of the gSr is discussed in the light of literature dealing with this phenomenon.